2021
DOI: 10.3389/fphys.2021.643580
|View full text |Cite
|
Sign up to set email alerts
|

Early Growth and Protein-Energy Metabolism in Chicken Lines Divergently Selected on Ultimate pH

Abstract: In chickens, a divergent selection on the Pectoralis major pHu allowed the creation of the pHu+ and pHu− lines, which represent a unique model for studying the biological control of carbohydrate storage in muscle. The present study aimed to describe the early mechanisms involved in the establishment of pHu+ and pHu− phenotypes. At hatching, pHu+ chicks were slightly heavier but exhibited lower plasma glucose and triglyceride and higher uric acid. After 5 days, pHu+ chicks exhibited higher breast meat yield com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…This environment can affect the physiological and morphological development of embryos, with substantial effects on the development of chick phenotypes 17 . At hatching, the divergent lines selected based on breast meat pHu already present distinct phenotypic and metabolic features 5 , which may result from quantitative and qualitative differences in available nutrients in ovo and/or their use by the embryo. To test this hypothesis, we first investigated the potential line-related differences in egg characteristics, including the composition of the yolk and amniotic fluid, which are the two main sources of nutrients during egg incubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This environment can affect the physiological and morphological development of embryos, with substantial effects on the development of chick phenotypes 17 . At hatching, the divergent lines selected based on breast meat pHu already present distinct phenotypic and metabolic features 5 , which may result from quantitative and qualitative differences in available nutrients in ovo and/or their use by the embryo. To test this hypothesis, we first investigated the potential line-related differences in egg characteristics, including the composition of the yolk and amniotic fluid, which are the two main sources of nutrients during egg incubation.…”
Section: Discussionmentioning
confidence: 99%
“…This difference was associated with specific blood and muscle metabolic profiles, indicating greater protein catabolism and lipid oxidation in the pHu+ line and greater activation of the glycolytic pathway in the pHu− line 4 . Recently, it has been shown that the divergent metabolic pattern of pHu+ and pHu− lines is set in early during development since, at hatching, the two lines already show differences in protein and energy metabolism that could be related to a different ability to use energy sources at the muscle level 5 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in chickens selected for divergence in abdominal fat pad by Dupont et al (27), changes in liver metabolism were observed to favor lipogenesis and ultimately greater abdominal fat deposition. Meat quality-focused work in broilers has shown that divergent selection for breast ultimate pH at harvest resulted in differences in carbohydrate and protein metabolism, specifically by altering glucose storage and key enzymes in both the mitochondrial respiration and glycolytic pathways (28). Additionally, lipid metabolism is shown to be dysregulated in broilers affected by the woody breast myopathy, an unintended consequence of selection for increased breast yield (29).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in 2004, the genome sequencing of chicken wherein scientists had estimated 20000 to 23000 genes for chicken was released [ 23 ]. As a potential source of protein, many efforts have been made for both embryonic and adult chickens, ranging from the growth rate to meat yield, and the feeding strategies and efficiencies [ 24 26 ]. Studies have shown that breast muscle’s in vivo glycogen content correlates with meat quality [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a potential source of protein, many efforts have been made for both embryonic and adult chickens, ranging from the growth rate to meat yield, and the feeding strategies and efficiencies [ 24 26 ]. Studies have shown that breast muscle’s in vivo glycogen content correlates with meat quality [ 24 ]. On the other hand, it has been reviewed that continuous progress in optimizing meat and egg production has led to various disorders in metabolism and reproduction; then it has negative implications on humans as a result of consuming chicken’s meat and egg [ 25 ].…”
Section: Introductionmentioning
confidence: 99%